Studies on Amylase Activity of Pancreatin Obtained from Bovine Pancreas - Iqbal, Lubna; Niazi, Zaman; Siddiqui, Kauser; Lateef, Mehreen (Biological Sciences - PJSIR, 2008)
The main objective of this study was to prepare pancreatin in liquid and powder form and to determine its amylase activity in crude homogenate of animal tissue. Different conditions were optimized for estimation of maximal activity including pH, temperature and substrate concentration. The optimum pH was found to be 6.8. The enzyme was optimally active at 50 °C. The effect of substrate concentration on enzyme activity was also studied and Km was found to be 0.5%.